Exploring the Efficacy of Vocational Training Programs in Motor Vehicle and Mechanic Works Trade: A Case Study of Science and Technical Colleges in Northeast Nigeria - Sule, Samaila Yerima; Lare, Ojo Joshua; Oguntokun, John Ebenezer (Darul Yasin Al Sys, 2024)
This study aimed to explore the efficacy of vocational training programs in Motor Vehicle and Mechanic Works Trade: a case study of science and technical colleges in northeast Nigeria. The study adopted a survey research design and was carried out in northeast Nigeria. The Zone includes the states of Adamawa, Bauchi, Borno, Gombe, Taraba, and Yobe, and is situated at latitude 6.260 East and longitude 4.920 North East of Nigeria. The population of the study was 621 comprising 128 MVMW trade teachers, 126 administrators (Principals and two Vice Principals), and 367 students from the 42 science and technical colleges in Northeast Nigeria. The study adopted Simple random sampling to select a sample size of 234 respondents using Krejcie and Morgan (1970) sample size table. The instrument for data collection was a structured questionnaire titled: “Efficacy of Vocational Training Programs in Motor Vehicle and Mechanic Works Trade Questionnaire, (EVTPMVMWTQ)